HUBUNGAN POLA ASUH DEMORKATIS ORANG TUA DENGAN PERILAKU MORAL ANAK USIA 4-6 TAHUN - Lutfiah Zuhra; Hapidin Hapidin (STIT Al-Marhalah Al-Ulya Bekasi, 2022)
This study aims to determine the relationship of democratic parenting parents with the moral behavior of 4-6 years old children. This research was conducted in Lenteng Agung Village, South Jakarta. The sample in this study were parents who have children aged 4-6 years who attend school in Lenteng Agung Village, South Jakarta as many as 30 people. This research was using cluster simple random for the sampling technique. The method used is the correlation method. Data was collected by distributing questionnaires in the form of questionnaires. From the calculation results of the Pearson Product Moment correlation test, the results of the person correlation r are 0.378 and Â are 0.361 with a significant level = 0.05 and n is 30. From the results of data analysis, it can be concluded that there is a significant positive relationship between parenting democratic parents with the moral behavior of 4-6 years old children in Lenteng Agung Village, South Jakarta.Â Keywords: democratic parenting of parents, moral behavior